2017
DOI: 10.1016/j.ejvs.2017.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Wall Shear Stress in Aortic Type B Dissection May Relate to Retrograde Aortic Type A Dissection: A Computational Fluid Dynamics Pilot Study

Abstract: Increased WSS accompanies the occurrence of RTAD. The results merit the design for a prospective study to confirm whether WSS is a risk factor for the occurrence of RTAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 20 publications
(19 reference statements)
4
36
0
Order By: Relevance
“…Flow patterns play a key role in the development and progression of TBAD, with hemodynamic features being associated with complications and outcomes of TEVAR [17]. Our results showed that large recirculation regions occurred in the FL close to the tears, suggesting the possibility of further FL thrombosis at these locations.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Flow patterns play a key role in the development and progression of TBAD, with hemodynamic features being associated with complications and outcomes of TEVAR [17]. Our results showed that large recirculation regions occurred in the FL close to the tears, suggesting the possibility of further FL thrombosis at these locations.…”
Section: Discussionmentioning
confidence: 65%
“…WSS is a key driver of aortic remodeling [16], which can strongly influence the formation and advancement of aortic dissections. High WSS has been associated with tear initiation [8] and the occurrence of retrograde type A aortic dissection [17], whilst low WSS is a key factor in FL thrombosis [14,15,17]. On the other hand, pressure is an important predictor of disease outcomes [18], as a high pressure imbalance between true and false lumen could cause true lumen collapse or aortic wall rupture.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study by Osswald et al found that increased wall shear stress accompanied the occurrence of retrograde dissection in patients with type B aortic dissection. 30 Moreover, the presence of a BA variant seems to be associated with haemodynamic patterns, indicating increased vascular stiffness. 24 In summary, some of the post-TEVAR deaths could reasonably be associated with BA, as BA poses severe technical challenges.…”
Section: Discussionmentioning
confidence: 99%
“…Different pathologies, diseases, vascular districts, and ultimately available measures in this respect lead to different strategies, and the identification of the optimal approach for different problems (and different purposes) is far from being reached, subject of the recent literature. 7,[14][15][16][17][18] In particular, treatment of boundary conditions shows a wide variety of approaches from an extremely simplified stress-free approach in the outflow boundaries 19,20 to sophisticated data assimilation techniques such as Kalman filtering. 21 The aim of this article is to present, validate, and test an algorithm for calibrating boundary conditions in thoracic aortic simulations based on the so-called three-element Windkessel model (3WK) and a minimization approach proposed by Toorop et al 22 In fact, the recent article by Pirola et al, 18 though using a different calibration strategy, has confirmed the strength of using 3WK circuits as outflow boundary conditions against other methodologies.…”
Section: Introductionmentioning
confidence: 96%
“…Different pathologies, diseases, vascular districts, and ultimately available measures in this respect lead to different strategies, and the identification of the optimal approach for different problems (and different purposes) is far from being reached, subject of the recent literature . In particular, treatment of boundary conditions shows a wide variety of approaches from an extremely simplified stress‐free approach in the outflow boundaries to sophisticated data assimilation techniques such as Kalman filtering …”
Section: Introductionmentioning
confidence: 99%